Studying the Changes in Physical Functioning and Oxidative Stress-Related Molecules in People Living with HIV after Switching from Triple to Dual Therapy - Jessica Cusato; Anna Mulasso; Micol Ferrara; Alessandra Manca; Miriam Antonucci; Guido Accardo; Alice Palermiti; Gianluca Bianco; Francesco Chiara; Jacopo Mula; Maria Grazia Maddalone; Maria Cristina Tettoni; et al. (MDPI AG, 2024)
Background: Physical activity could increase the production of oxidative stress biomarkers, affecting the metabolism and excretion of antiretroviral drugs and, consequently, the clinical outcome. Nowadays, people living with HIV (PLWH) are mostly switching from triple to dual therapy, but no data are available in terms of physical functioning and oxidative stress. The aim of this study was to evaluate if some antioxidant biomarkers and physical functioning tests could be different according to triple or dual antiretroviral therapy. Methods: PLWH were evaluated at baseline (BL), while treated with three drugs, and six months after the switch to dual therapy. Physical functioning was quantified using validated tools. Mitochondrial and cytosol antioxidant molecules were evaluated through liquid chromatography. Results: Twenty-five patients were analyzed. A statistically significant difference between triple and dual therapy was found for mitochondrial glutathione, but not for physical tests. Evaluating differences between physically active and inactive individuals, the following statistically significant differences were suggested, considering triple therapy (mitochondrial n-formyl-methionine p = 0.022, triglycerides p = 0.023) and double therapy (mitochondrial glycine p = 0.035, cytosol glutamic acid p = 0.007, cytosol s-adenosylmethionine p = 0.021). Conclusions: For the first time, this study suggests possible differences in terms of antioxidant molecules and physical functioning in PLWH switching from triple to dual therapy.